Recent Trends in the Foliar Spraying of Zinc Nutrient and Zinc Oxide Nanoparticles in Tomato Production - Razu Ahmed; Mohd Yusoff Abd Samad; Md. Kamal Uddin; Md. Abdul Quddus; M. A. Motalib Hossain (Agronomy, 2021)
Growing vegetables can be seen as a means of improving people’s livelihoods and nutritional status. Tomatoes are one of the world’s most commonly planted vegetable crops. The nutritional arrangement of the tomato depends on the quantity and type of nutrients taken from the growing medium, such assoil and foliar application; therefore, an adequate amount of macro- and micro-nutrients, including zinc (Zn) and zinc oxide nanoparticles (ZnO-NPs), are crucial for tomato production. Zinc foliar spraying is one of the effective procedures that may improve crop quality and yield. Zinc oxide nanoparticles (ZnO-NPs) are represented as a biosafety concern for biological materials. Foliar application of Zn showed better results in increasing soluble solids(TSS), firmness, titratable acidity, chlorophyll-a, chlorophyll-b, ascorbic acid, amount of lycopene. Researchers have observed the effect of nanoparticles of zinc oxide on various crops, including tomatoes. Foliar spraying of ZnO-NPs gave the most influential results in terms of best planting parameters, namely plant height, early flowering, fruit yields as well as lycopene content. Therefore, more attention should be given to improving quantity and quality as well as nutrient use efficiency of Zn and ZnO-NPs in tomato production. Recent information on the effect of zinc nutrient foliar spraying and ZnO-NPs as a nano fertilizer on tomato productivity is reviewed in this article.